CAN ETHICAL LEADERSHIP USING THE PERSON-ORGANIZATION FIT AS A MEDIATING ROLE ENCOURAGING SUBORDINATE ETHICAL BEHAVIOR? - Maria Helena Carolinda Dua Mea (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This research seeks to (1) understand how ethical leadership affects employee ethical behavior, (2) how it affects person-organization fit, (3) how it affects ethical behaviour, and (4) how it mediates between ethical management and ethical review. This study is quantitative. Disseminating questionnaires collects quantitative data, while qualitative data is collected by observing the research site, interviewing Credit Corporation managers and chief managers, and reviewing relevant literature. The questionnaire, the primary data collection instrument, measures ethical leadership, employee ethics, and Person-Organization Fit with 15 indicators. A credit cooperative officer in Ende, a community of 39 inhabitants, was sampled. They come from Ende's six credit cooperatives. Data was analyzed using SmartPLS 4.0.1. The track coefficient test showed that ethical leadership variables positively affect person-organization fit, ethical behavior, and ethical actor variables, and that ethical leadership variables positively influence employee ethical behaviour through person-organization fit as mediation. According to the R-Square test, ethical leadership and person-organization fit influenced employee ethical behavior by 42%, while other variables influenced the remaining 58%. The test results showed that ethical leadership has a positive and significant effect on person-organization fit, an ethical influence and significant effect on the ethical behavior of Credit Cooperative employees in Ende, a positive but non-significant effect on employee ethical behaviour, and a positive but non-significant effect on employee ethical behavior through person-organization fit.